Synthesis and characterization of α-d-Galp-(1 → 3)-β-d-Galp epitope-containing neoglycoconjugates for chagas disease serodiagnosis. (15th May 2019) - Lopez, Rosana; Giorgi, M. Eugenia; Melgarejo, Linda Toro; Ducrey, Ivana; Balouz, Virginia; González-Salas, Diego; Cámara, María de los Milagros; Buscaglia, Carlos A.; de Lederkremer, Rosa M.; Marino, Carla
Abstract: The immunodominant epitope α-d -Gal p -(1 → 3)-β-d -Gal p -(1 → 4)-d -GlcNAc, expressed in the mucins of the infective trypomastigote stage of Trypanosoma cruzi has been proposed for multiple clinical applications, from serodiagnosis of protozoan caused diseases to xenotransplantation or cancer vaccinology. It was previously shown that the analogue trisaccharide, with glucose in the reducing end instead of GlcNAc, was as efficient as the natural trisaccharide for recognition of chagasic antibodies. Here we describe the synthesis of α-d -Gal p -(1 → 3)-β-d -Gal p -(1 → 4)-d -Glc p functionalized as the 6-aminohexyl glycoside and its conjugation to BSA using the squarate method. The conjugate of 6-aminohexyl α-d -Gal p -(1 → 3)-β-d -Gal p was also prepared. Both neoglycoconjugates were recognized by serum samples of Trypanosoma cruzi -infected individuals and thus, are promising tools for the improvement of Chagas disease diagnostic applications. Graphical abstract: Image 1 Highlights: α-d -Galp(1 → 3)-β-d -Galp(1 → 4)-d -GlcNAc is a main component of Trypanosoma cruzi trypomastigote mucins with immunological properties. Analogue α-d -Gal p (1→3)-β-d -Gal p (1→4)-β-d -Glc p and a-d -Gal p (1-3)-b-d -Gal p derivatized as 6-aminohexyl glycoside were conjugated to BSA by the squarate method. ELISA assays showed that these neoglycocojugates were recognized by sera from chagasic patients.